‘I think I’m gonna hurl’: A Narrative Review of the Causes of Nausea and Vomiting in Sport - Wilson, Patrick B. (Sports (Basel), 2019)
Exercise-associated gastrointestinal (GI) distress can negatively impact athletic performance and interfere with exercise training. Although there are a few universal underlying causes of GI distress, each symptom often has its own unique triggers and, therefore, its own prevention and management strategies. One of the most troubling GI symptoms an athlete can experience during training and competition is nausea/vomiting. The prevalence of nausea varies with several factors, two of the most important being exercise intensity and duration. Relatively brief, high-intensity exercise (e.g., sprinting, tempo runs) and ultra-endurance exercise are both associated with more frequent and severe nausea. The potential causes of nausea in sport are numerous and can include catecholamine secretion, hypohydration, heat stress, hyponatremia, altitude exposure, excessive fluid/food consumption, hypertonic beverage intake, pre-exercise intake of fatty- or protein-rich foods (especially in close proximity to exercise), prolonged fasting, various supplements (caffeine, sodium bicarbonate, ketones), certain drugs (antibiotics, opioids), GI infections, and competition-related anxiety. Beyond directly addressing these aforementioned causes, antiemetic drugs (e.g., ondansetron) may also be useful for alleviating nausea in some competitive situations. Given the commonness of nausea in sport and its potential impact on exercise performance, athletes and sports medicine practitioners should be aware of the origins of nausea and strategies for dealing with this troublesome gut complaint.